PERTUMBUHAN EKONOMI VS EKSPOR SEKTORAL INDONESIA PASKA OIL BOOM: UJI KAUSALITAS DAN STUDI KOMPARATIF DENGAN THAILAND DAN MALAYSIA - Musaiyadi, Musaiyadi (Journal of Indonesian Economy and Business, 2005)
The changing of Indonesiaâs industrialization policy from inward oriented (importsubstitution) to outward oriented (export oriented) strategy has delivered Indonesia success in increasing its export within two last decade. Moreover, this strategy also has changed the composition of Indonesiaâs export from primary based products (oil and agriculture) to secondary based products (manufacture).This study examines how so far the causality relationship between national income ofIndonesia and export by sector (agriculture, oil, and manufacture), and than comparingthis with Thai and Malaysia as LDCs in Asian. By using Grangerâs causality test modifiedby Hsioâs criteria on quarterly data from 1982.1 â 2002.4, this paper concludes: (1)Indonesiaâs national income influences its industrial export positively, (2) Thaiâs nationalincome influences its agricultural export positively, and (3) Malayâs industrial exportinfluences its national income positively, and Malayâs national income influences itsindustrial export negatively.The result of this study shows that the change of structural transformation from primarybased export (agriculture and oil) to secondary based export (manufacture) in stimulatingeconomic growth has been achieved by Malaysia. In contrast, this strategy is not occurredin Indonesia and Thailand. In the other word, export for Indonesia and Thailand is just aprogressive process in stimulating economic growth, not to be an essential factor inconstructing economic growth.Keywords: Economic Growth, Export, Structural Transformation